2023
DOI: 10.1002/smll.202300154
|View full text |Cite
|
Sign up to set email alerts
|

Laser CVD Growth of Uniquely <010>‐oriented β‐Ga2O3 Films on Quartz Substrate with Ultrafast Photoelectric Response

Abstract: The oriented growth of β‐Ga2O3 films has triggered extensive interest due to the remarkable and complex anisotropy found in the β‐Ga2O3 bulks. Remarkable properties, including stronger solar‐blind ultraviolet (SBUV) absorption, better mobility, and higher thermal conductivity, are usually observed along <010> direction as compared to other low‐index axes. So far, <010>‐oriented β‐Ga2O3 film growth has been hindered by the lack of suitable substrates and higher surface energy of the (010) crystal plane. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…38,39 Here, the lattice mismatch is defined as δ = (a epi − a sub )/a sub , where a epi and a sub represent the lattice parameters of the epitaxial layer and the substrate, respectively. As shown in panels a and d of Figure 3, the surface morphology of (010)-plane β-Ga 2 O 3 samples T 1.5 and T 3 exhibits a three-dimensional (3D)-structured roof-like feature, which is similar to the (010)-plane results reported by Tu et al 22 but differs from both the (−201)-plane results reported by Tang et al 40 and the SEM surface image of comparison sample T C6 (see Figure S4 of the Supporting Information). As shown in panels b, c, e, and f of Figure 3, the cross-sectional SEM images and energy-dispersive X-ray spectrometry (EDS) mapping images for samples T 1.5 and T 3 were measured and their layer structures were determined from the measurement procedure and EDS mapping images.…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
See 3 more Smart Citations
“…38,39 Here, the lattice mismatch is defined as δ = (a epi − a sub )/a sub , where a epi and a sub represent the lattice parameters of the epitaxial layer and the substrate, respectively. As shown in panels a and d of Figure 3, the surface morphology of (010)-plane β-Ga 2 O 3 samples T 1.5 and T 3 exhibits a three-dimensional (3D)-structured roof-like feature, which is similar to the (010)-plane results reported by Tu et al 22 but differs from both the (−201)-plane results reported by Tang et al 40 and the SEM surface image of comparison sample T C6 (see Figure S4 of the Supporting Information). As shown in panels b, c, e, and f of Figure 3, the cross-sectional SEM images and energy-dispersive X-ray spectrometry (EDS) mapping images for samples T 1.5 and T 3 were measured and their layer structures were determined from the measurement procedure and EDS mapping images.…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…However, the growth of (010)-plane β-Ga 2 O 3 is challenging as a result of its higher surface energy rather than other planes and the lack of a suitable substrate with a small lattice mismatch with (010)plane β-Ga 2 O 3 . 22 In this study, (010)-plane β-Ga 2 O 3 was successfully thermally oxidized using nonpolar (110) a-plane GaN for the first time. Its structural properties were characterized by Xray diffraction (XRD) and scanning electron microscopy (SEM).…”
Section: ■ Introductionmentioning
confidence: 90%
See 2 more Smart Citations